Current Phase Relation of Y1Ba2Cu3O 7-δ Step Edge Junction; IEEE Transactions On Applied Superconductivity; Vol. 5, iss. 2 - Polushkin V.; Uchaykin S. V. Sergey Victorovich; Knappe S.; Koch H. (1995, 1995)
Title screen